Pengembangan Silabus Selaras CEFR untuk Mengoptimalkan Pembelajaran Bahasa Arab di Pesantren Mahasiswa X - Batrisyia, Azra; Suganda, Sonya Puspasari (JURNAL Al-AZHAR INDONESIA SERI HUMANIORA, 2025)
Textbook-based instruction fails to address students' actual needs, and the lack of a clear learning sequence highlights the need for a structured syllabus. This study develops an Arabic syllabus to improve instruction at Pesantren Mahasiswa X using a research and development approach.  The methods of data collection used were interviews, focus group discussion, and questionnaire with key stakeholders, including students, alumni, teachers, the principal, and the foundation. Thematic analysis of the needs analysis revealed that: 1) instruction aims to develop simple communication skills and subsequently, comprehension of Islamic texts; 2) learning levels require clear specification; and 3) instruction should initially focus on listening and speaking skills to address immediate needs. The study produced a competency-based syllabus aligned with the Common European Framework of Reference for Language (CEFR) for beginner level. The syllabus includes a program description, objectives, assessments, topics, learning outcomes, linguistic competencies, activities, indicators, and learning media. This article also discusses CEFR alignment and challenges encountered in syllabus implementation. Keywords - Arabic syllabus design, competency-based syllabus, CEFR, need analysis